The Influence of Training And Motivation on The Performance of PKH Assistant in Gorontalo Regency Mediated By Remuneration - Ainsyah Parasmitha Tahir Rauf; Deni Gustiawan; Asep Saefudin; Mulyadi Mulyadi (Green Publisher Indonesia, 2025)
This study aims to evaluate the extent to which the training provided to the Program Keluarga Harapan (PKH) facilitators can improve their performance, as well as how the motivation possessed by PKH facilitators affects their performance. Additionally, this study also evaluates the role of remuneration in mediating the relationship between training, motivation, and the performance of PKH facilitators. This study uses simple random sampling technique with the population of PKH facilitators. Each member of the population has an equal chance of being selected as a sample. The approach used in this study is Structural Equation Model (SEM) with measurement model using Smart PLS version 3.2.9. The results of the study indicate that motivation and remuneration are important factors influencing the performance of PKH facilitators. However, training does not have a significant impact on performance, either directly or indirectly through remuneration. These findings suggest that to improve the performance of PKH facilitators, greater attention should be given to enhancing motivation and remuneration.